Sekolah Luar Biasa Tunagrahita Di Pekanbaru Dengan Pendekatan Arsitektur Perilaku - Jenny Yolanda Gustia; Ratna Amanati; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Intellectual dissabilities school is an institution of formal education that caters for children with mental retardation. To solve the problem of designing a room needed by the children with intellectual dissabilities, is with architectural behavior approach for the children with intellectual dissabilities. This research uses the theory of behavioral architecture, the theory of children with intellectual dissabilities behavior in children withintellectual dissabilities learning books and theory of optimal quality room. The design method is using concept of optimal quality room. The optimal quality room includes the activity of the children with intellectual dissabilities, magnitude characteristics of children with intellectual dissabilities, accessibility, site zone, colour, temperature and lighting, sizeand shape, furniture and its arrangement. Designing intellectual dissabilities school has met and accommodate the needs of the children with intellectual dissabilities according to their mindset and character.Key words: Mentally School, Intellectual Dissabilities, Behavioral Architecture, Optimal Quality Room